A phenomenological account of the formation of self through interplay of memories and life - Stacey, Keith Lindsay (Curtin University, 2016)
This thesis is a phenomenological inquiry that charts the researcher’s journey through the world of work to what that might constitute the lived experiences of Everyman within a full range of contexts, from factory hand to knowledge worker. It includes a process of re-collection of memories and attempts to reconcile the protagonist with himself through narrative inquiry. Phenomenological reflection accompanies the narrative and demonstrates both the uniqueness and universality of the researcher/protagonist’s personal experiences.